2001
DOI: 10.1097/00000637-200111000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Levels of Subatmospheric Pressure on the Rate of Granulation Tissue Formation in Experimental Wounds in Swine

Abstract: The use of subatmospheric pressure to promote wound healing has increased in popularity during the last several years. The original studies on granulation tissue formation used a 125-mmHg vacuum. The use of alternative sources of subatmospheric pressure has led to many questions regarding efficacy or risk. In this report a swine model is used to quantify and compare the effects of low vacuum suction (25 mmHg) and high vacuum suction (500 mmHg) produced by various vacuum pumps and wall suction systems with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
2
26

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(250 citation statements)
references
References 5 publications
3
219
2
26
Order By: Relevance
“…Several studies have shown intermittent pressure mode to be more efficacious compared to continuous negative pressure. 20 The wound was opened every fourth day for reapplication of dressing and swab was sent for aerobic and anaerobic culture every time the wound was opened. Once the wound had sufficient granulation tissue such that it could undergo skin grafting or the wound had contracted to such a size that it could surgically closed, it was either closed or covered with skin graft.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown intermittent pressure mode to be more efficacious compared to continuous negative pressure. 20 The wound was opened every fourth day for reapplication of dressing and swab was sent for aerobic and anaerobic culture every time the wound was opened. Once the wound had sufficient granulation tissue such that it could undergo skin grafting or the wound had contracted to such a size that it could surgically closed, it was either closed or covered with skin graft.…”
Section: Methodsmentioning
confidence: 99%
“…The studies 3,26,29 reported in this review applied pressure of -125 mmHg to surgical spinal wounds. Morykwas et al 40 found -125 mmHg was associated with higher rate of granulation formation in an experimental pig model, but McCord et al 41 suggested wound healing could be achieved using lower negative pressure (-100 mmHg) in infants and children. The general consensus in the literature (mainly for non-spinal wounds) indicated a negative pressure of -50 to -75 mmHg to be used in children 2 years or younger; -75 to -125 mmHg for children above 2 and -100 to -125 mmHg is used in adult patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Morykwas et al [41], in histologic studies regarding burns in a porcine model, described preservation of tissue with negative pressure wound therapy otherwise destined for necrosis (controls) [40]. Implied is the cascade of molecular events that occur after a thermal wound characterized by edema, impaired microcirculation, and heightened capillary afterload (reperfusion injury) with secondary necrosis and additional tissue loss [40,51,53].…”
Section: Corroborations From Basic Science and Other Disciplinesmentioning
confidence: 99%
“…In 1997, the FDA approved negative pressure wound therapy. Subsequently, animal studies [39,41] and additional clinical reports that favored negative pressure wound therapy to reduce edema, decrease bacterial loads, increase granulation tissue formation, and other pathways to promote wound healing [2,38] were published. The majority of studies however, regard chronic or diabetic wounds [5,8,18,42,43,52].…”
Section: Introductionmentioning
confidence: 99%